IMPROVEMENT OF THE FORENSIC MEDICAL DIAGNOSIS OF THE PRESCRIPTION OF SOFT TISSUE INJURIES BASED ON QUANTITATIVE MORPHOMETRIC CRITERIA - Ruziev Sh.I.; Mukhsinova M.Kh.; Djalilova G.R. (Central Asian Journal of Medicine, 2025)
Determining the prescription of soft tissue injuries is one of the most difficult and urgent problems of modern forensic medical examination. Accurate temporal assessment of traumatic effects is crucial in the investigation of crimes against life and health, establishing the sequence of events in accidents, as well as verifying the testimony of participants in the incident and witnesses. This information often becomes key in determining the cause-and-effect relationships between injury and the consequences that have occurred, which directly affects the qualification of the act in the criminal law aspect.